Patterns of accumulation of knowledge and innovation in the brazilian textile-garment complex - Gonçalves, Eduardo; Lemos, Mauro Borges; Amaral, Pedro Vasconcelos; Guelber Fajardo, Bernardo de Abreu (Revista Econômica do Nordeste, 2016)
This paper explores the patterns of technological knowledge accumulation of the textile-garment complex in Brazil in order to suggest industrial policies to reinforce the firms' competitiveness. The paper is based on micro-data from the Technological Innovation Survey (Pintec) and the Yearly Industrial Survey (PIA) of the Brazilian Institute for Geography and Statistics (IBGE) in 2005, through which Brazilian firms were classified as leaders, followers, fragiles and emerging companies. The results show the presence of strong inter and intrasectorial heterogeneity and suggest that measures for technological policies should obey the different patterns of technological knowledge accumulation in each of these firm’s categories.